Monitoring and Conservation of Freshwater and Marine Fishes: Synopsis - Robert L. Vadas; Robert M. Hughes (Fishes)
Globally, native migratory and resident fishes are declining from aquatic and terrestrial ecosystem degradation resulting from physicochemical habitat alteration, migration barriers, over-exploitation, hatchery supplementation, non-native species introductions, and the climate crisis [...]